Determinant Factors Influencing Teacher Performance in the Digital Era - Milatun Nadifa; Mustiningsih Mustiningsih; Raden Bambang Sumarsono (Universitas Muhammadiyah Mataram, 2024)
This study aims to examine the factors influencing teacher performance in the digital age, focusing on both supportive and obstructive elements shaping their effectiveness in integrating digital tools into teaching practices. The research systematically examines how technological and pedagogical factors, personal factors, organizational support, contextual factors, technostress, and the digital divide impact teacher performance. A systematic literature review was conducted using PRISMA guidelines, analyzing 650 scholarly articles published between 2020 and 2024. Articles were sourced through the Publish or Perish (PoP) application, applying specific inclusion criteria, such as empirical studies published in accredited journals and relevance to the study objectives, while excluding articles that lacked methodological rigor or were not written in English or Indonesian. From this process, 94 high-quality articles were selected for analysis. Data were processed using a scoring matrix to assess article quality and relevance, and findings were systematically categorized using Microsoft Excel to generate narratives, tables, and diagrams. The results reveal six critical factors affecting teacher performance: technological and pedagogical competence, personal factors, organizational support, contextual factors, technostress, and the digital divide. These findings highlight the complexity of teacher performance in the digital age and underscore the necessity of institutional support, continuous professional development, and policies to address technology-related disparities and stress. This study provides valuable insights for designing evidence-based strategies to enhance teacher effectiveness and educational quality in the era of digital transformation.